A prospective multicentre study of healthcare provider preference in rapid HIV testing kits: Determine versus INSTI. (January 2018) - Amyai, N; Darling, KEA; D'Acremont, V; Castro, E; Ebert, S; Diserens, M Monnat; Perdrix, J; Fossati, A Hérard; Bodenmann, P; Cavassini, M
Rapid HIV testing may circumvent the practical barriers to HIV testing in several settings. User preference of the testing kits available has been relatively underexplored. We examined healthcare provider (HCP) ratings of two validated rapid testing kits in clinical practice. From 1 July to 1 December 2012 we prospectively recruited HCPs (clinic nurses) from three outpatient clinics linked to Lausanne University Hospital, Lausanne, Switzerland. The HCPs had experience in taking blood samples but varying experience in rapid HIV testing. Participating HCPs performed rapid HIV testing using Determine™ Combo (DETE) or INSTI™ (INSTI), according to a predefined randomization sequence, and rated practical aspects of each test using a Likert scale. Seventeen HCPs of 23 approached (74%) were eligible and agreed to participate, performing a total of 336 HIV tests. Globally, the testing procedure was rated as easy or very easy by 97% (DETE) to 99% (INSTI) of tests performed. Among experienced HCPs, DETE was rated easier than INSTI for kit storage (p < 0.001) and blood collection ( P = 0.012) while INSTI was rated easier than DETE for blood application ( P = 0.001) and test interpretation ( P = 0.005). Among less experienced HCPs, both tests performed equally with the exception of test interpretation ( P < 0.001) and overall ease of use ( P = 0.05) in favour of INSTI. Of all HCPs, 94% stated they would recommend INSTI over DETE based on the time to result, ease of test interpretation and overall ease of use. Rapid HIV testing was considered easy to perform, even by inexperienced nursing staff. Whilst both tests were considered easy to use, the HCPs in this study preferred INSTI to DETE overall, due to rapid time to result, ease of test interpretation and general ease of use.